The Socio-Legal Implications of Digital Death and Data Inheritance - Imala, Yanti Desi; Novrianda, Finda; Sujito, Fino Gani; Axelasia, Leni (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Digital identity after biological death raises significant questions regarding the question of ownership, access, and inheritance of data. Objects of digital properties, to include social media profiles, cloud storage, and online transaction histories, are now practically inseparable from personal identity. However, these questions regarding accessing postmortem data are still underdeveloped in legal and policy terms. The objective of this study is to investigate the socio-legal implications of digital death using the interplay of social norms, legal systems, and digital platform policies. The qualitative exploratory case study method was used to collect data employing semi-structured interviews with bereaved families, legal specialists, and representatives from technology platforms. Hematic analysis yields five core findings: legal access generally requires court orders; public awareness of digital inheritance is minimal; jurisdictional variation creates confusion; digital accounts are memorialized spaces; and there are ethical tensions between postmortem privacy and family rights. The study concludes that social norms currently develop more responsively than legal or technical systems, with the result being informal but risky practices on the part of families. This research contributes an integrative socio-legal framework to guide inclusive and ethical digital inheritance policy. It requires harmonized law, public literacy, and cross-platform collaboration to maintain human dignity and digital rights after death.